Harnessing the Power of Green Open Access: Implementing the ‘Taverne’ law in the Dutch Academy - de Vries, Mark Leon (Septentrio Conference Series, 2018)
Watch the VIDEO. In 2015 the Dutch parliament passed an amendment to the national copyright laws that – at least in theory – significantly expanded the scope for publishing in green open access. Known for its main sponsor, Joost Taverne, this amendment grants the author of any ‘short work of science’ that has been ‘funded by the Dutch government’ a legal right to make this work ‘freely available to the public’, following ‘a reasonable term’ after its original publication. Crucially, the author retains this right regardless of the terms and conditions of the original publisher. Although this amendment has been in force for over three years, it has not had much practical effect to date. On the one hand this is due to competing institutional priorities at that time and on the other hand because the amendment’s terms are too vague to be of much use to individual researchers. In order to harness the potential of the law, the Association of Universities in the Netherlands (VSNU) and the National Platform Open Science have launched a project that aims to: • Establish clear and concrete guidelines for interpreting the amendment; • Make roughly 5% of all academic output in the Netherlands that falls within these guidelines freely available through university repositories; • Test the response of publishers to the implementation of the amendment; • Establish jurisprudence in case publishers decide to take legal action against either the universities or individual scholars; and • Ultimately accelerate a broader shift toward universal and affordable gold open access as the default standard in academic publishing. Ultimately this project thus seeks to use the power of green open access not for its own sake, but as a wedge to encourage publishers to make the transition to an efficient and affordable Gold Open Access model. Meanwhile it offers a workable alternative to researchers who encounter obstacles to publishing gold. This presentation will discuss the unique opportunities this amendment provides to radically change the publishing landscape, as well as the legal, technical and organizational challenges involved in practically implementing the amendment’s potential, based on the (ongoing) experience of the VU University’s local project team. Hopefully this will spark a discussion on the international implications and possible opportunities to develop similar initiatives in different national – and thus legal – contexts. At the same time international input and experiences can help further refine and improve the project.